Reconstructing Disability Rights Paradigm: Harmonizing Pancasila’s Humanity Principle within the Global Constitutionalism Trend - Zahwa Purwa Anggita (Indonesian Journal of Pancasila and Global Constitutionalism, 2025)
Global constitutionalism has fundamentally shifted the paradigm of disability rights from a charity-based medical model to a rights-based social model, as epitomized by the UN Convention on the Rights of Persons with Disabilities (CRPD). However, the domestication of these global norms in Indonesia often faces friction with local cultural interpretations that still view disability through a lens of pity. This paper aims to harmonize the global standards of the CRPD with the local philosophical foundation of Indonesia, specifically the Second Principle of Pancasila (Kemanusiaan yang Adil dan Beradab). Using a normative legal research method with conceptual and comparative approaches, this study analyzes the compatibility between the "Just and Civilized Humanity" principle and the "Non-Discrimination" principle of the CRPD. The results demonstrate that the Second Principle of Pancasila inherently rejects the charity model, arguing that a "civilized" humanity requires the recognition of rights rather than the granting of compassion. Consequently, Pancasila serves not as a barrier but as a strengthening moral filter for global constitutionalism norms. The study concludes that interpreting disability rights through Pancasila strengthens the mandate for affirmative action and accessibility. Furthermore, this harmonization is crucial to ensure that the legal protection for persons with disabilities is not only formally regulated but also culturally accepted by the Indonesian society. It is recommended that the Constitutional Court utilizes this interpretation in future judicial reviews to abolish discriminatory regulations.